2013
DOI: 10.1111/1756-185x.12225
|View full text |Cite
|
Sign up to set email alerts
|

Systemic sclerosis, birth order and parity

Abstract: Aim: A recent study identified increasing birth order to be a risk factor for the development of systemic sclerosis (SSc). This finding supports the theory that transplacental microchimerism may be a key pathological event in the initiation of SSc. We investigated the relationship between birth order and parity and the age of onset of SSc in South Australia.Method: A retrospective analysis of patient data in the South Australian Scleroderma Register was performed. Data were obtained from a mailed questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
0
10
0
2
Order By: Relevance
“…The Australian studies of prevalence recruited patients from SA and NSW only, thus their generalizability to the wider Australian population is uncertain. Genetic and shared environmental factors may play a role in this high prevalence, although the studies to date have been inconclusive . In addition, there was only one study focusing on the epidemiology of SSc among the Indigenous population ( n = 5), demonstrating a similar prevalence to non‐Indigenous Australians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Australian studies of prevalence recruited patients from SA and NSW only, thus their generalizability to the wider Australian population is uncertain. Genetic and shared environmental factors may play a role in this high prevalence, although the studies to date have been inconclusive . In addition, there was only one study focusing on the epidemiology of SSc among the Indigenous population ( n = 5), demonstrating a similar prevalence to non‐Indigenous Australians.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic and shared environmental factors may play a role in this high prevalence, although the studies to date have been inconclusive. 4,5,19 In addition, there was only one study focusing on the epidemiology of SSc among the Indigenous population (n = 5), demonstrating a similar prevalence to non-Indigenous Australians. This is discordant with the prevalence of other CTDs, such as systemic lupus erythematosus, which has a higher reported prevalence among the Indigenous Australian population.…”
Section: Epidemiology and Overall Disease Characteristics Of Sscmentioning
confidence: 99%
“…Retrospektywną analizą objęto 387 pacjentek z SSc oraz 367 zdrowych kobiet. Badacze wykluczyli kolejność urodzenia, wielkość rodziny, liczbę ciąż, wiek pierwszej ciąży oraz płeć pierwszego dziecka jako czynniki istotne w epidemiologii i patogenezie SSc, zaznaczając jednocześnie, że niezbędne jest przeprowadzenie większego badania z dobrze dobraną grupą kontrolną [10].…”
Section: Discussionunclassified
“…However, the theory of fetal MC in SSc was not confirmed in the study by Russo et al The retrospective analysis covered 387 patients with systemic scleroderma and 367 healthy individuals. The authors excluded birth order, family size, parity, age at first pregnancy and the gender of the first child as relevant factors in the understanding of epidemiology and the pathogenesis of SSc, although they admitted that a larger study with a well-matched control population is required [10].…”
Section: Discussionmentioning
confidence: 99%
“…Then 3 studies 10,18,19 were excluded and 3 review articles [20][21][22] were also excluded for the absence of sufficient information about menstrual and reproductive factors. Totally, along with our study, 6 case-control studies 9,[11][12][13]23 including 3837 SSc patients and 13 914 controls were finally selected (including those from our own case-control study). The characteristics of the studies are shown in Table 3.…”
Section: Meta-analysismentioning
confidence: 99%